Análise do rendimento em sistemas de transmissão sem fio para aplicação em veículos elétricos - Mendonça, Fabrício Ferreira (2019)
The objective of this work is to analyze the behavior of a wireless power transfer system for applications in electric vehicles, using the principle of magnetic coupling. And in order to reach it, it was necessary to construct an inverter circuit so that the sending coil operates in magnetic resonance with the receiving coil. A computational routine was developed to calculate the efficiency of a resonant circuit, based on the physical and electrical parameters of the coils. The prototype consists of energizing a primary flat coil and performing the inductive transfer to the secondary coil, which may be the same size or not. Experimental results were collected, such as yield curves as a function of distance, transfer through metallic and non-metallic barriers, yields due to misalignment between coils, automotive battery charge, maximum transfer distances; and others. Such a system can bring many benefits for application in battery charging in electric vehicles in a practical way and with satisfactory yields when conducting wireless inductive transfer.